Turmoil in Turkey and Hungary's Relations with NATO : A Neoclassical Realist Perspective on the AKP and FIDESZ Period - Karaca, Bilal Bahadir; Druláková, Radka, 1973-; Dubský, Zbyněk, 1974-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Established in 1949 and expanding its presence in the post-Cold War era, NATO represents one of the most successful alliances of modern times. However, various challenges have emerged between the alliance and its members throughout its history. In the contemporary context, this is most evident in Turkey's and Hungary's relations with the alliance. During the AKP and FIDESZ governments, the turbulent nature of these two states' commitment to NATO has been particularly noteworthy. This thesis examines the tumultuous relations between Turkey and Hungary with NATO through the theoretical lens of Neoclassical Realism. By employing the process-tracing method, the research focuses on both the international systemic level and domestic dynamics, aiming to fill gaps in the existing literature by providing a multi-layered analysis. The dissertation addresses the problematic aspects of Turkey and Hungary's NATO relations as being primarily driven by international political developments while also discussing the complementary role played by domestic dynamics in the emergence of these issues. Thus, this research serves as an important study, offering a Neoclassical Realist glance not only on the Turkey-NATO and Hungary-NATO cases but also on the relations between NATO and its member states in a broader sense.
Vedoucí práce: Radka Druláková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor disert. práce]; disertace; dissertations